(untitled) - Siegel, Jeffrey (Hoboken, N.J., 2008)
Investing in Renewable Energy puts the depletion of finite resources such as oil, natural gas, and coal in perspective, and discusses how renewable energy solutions–from solar and wind to geothermal and biofuels–will usher in a new generation of wealth for investors and a new way of life for everyone. With this book, you'll discover various renewable energy technologies that are at the forefront of transitioning our energy economy, and learn how to profit from next-generation renewable energy projects and companies that are poised to take over where fossil fuels will leave off.
Keywords: Energy industries,Clean energy industries,Công nghiệp năng lượng.,Công nghiệp năng lượng sạch